Do COVID-19 responses associate with prior hazard experiences? An investigation among flood-vulnerable subsidized housing residents with digital vulnerability - Seungbeom Kang; Dabin Lee; Jooyoung Kim; Jiahn Lee; Jongho Won; Yan Wang (Frontiers in Public Health)
In light of the threat posed by the COVID-19 pandemic and the accompanying public health risks, understanding the mechanisms through which individuals discern accurate information about COVID-19 and adopt appropriate preventive behaviors has become an important research subject. However, few studies have directly examined the associations between the digital divide, previous experience of non-pandemic disasters, and preventive behaviors in response to COVID-19. This study focuses on two elements that may affect individuals’ responses to COVID-19: (1) digital capabilities and (2) prior experience of and preparedness for flood risk. This study analyzed survey data collected from 200 households residing in flood-vulnerable subsidized housing in Florida, USA. The findings demonstrate that proficiency in Internet search skills is strongly and positively associated with information-seeking and preventive behaviors against COVID-19, while social media usage skills did not produce the same association. Moreover, the variables that indicate experience with and risk mitigation for flood hazards are significantly associated with the diversity of channels used to search for COVID-19 risk information, information-seeking behaviors, and preventive actions. These results suggest that improving preparedness for non-pandemic events may also enable individuals to be better prepared for future pandemics. The findings provide several action-oriented policy implications for reducing the multiple forms of vulnerability to which residents of subsidized housing are exposed.